Pengaruh Karakteristik Tujuan Anggaran dan Komitmen Organisasi terhadap Kinerja Pemerintah Nagari - Putri Zainiah; Fefri Indra Arza (Universitas Negeri Padang, 2023)
This study aims to examine the effect of budget characteristics and organizational commitment on the performance of the nagari government in the nagari government in Dharmasraya Regency, the research sample was determined using the non-probability sampling method with a sample of 52 villages. Quantitative data is the data selected in this study in the form of written responses from the questionnaire. The source of data used is primary data obtained from the nagari government. Methods Questionnaire data was collected by giving a set of oral questions or written questions to respondents to answer. The results showed that budget participation, clarity of budget objectives, budget feedback and organizational commitment had an effect on the performance of the nagari government. Budget evaluation and the difficulty of budget objectives have no effect on the performance of the nagari government.